Self-Healing Supramolecular Flexible Network of Zn(II) Exploring Chemo-Responsiveness, Antimicrobial Efficiency, and Variable Microelectronic Device Performances - Saha, Deblina (Langmuir : the ACS journal of surfaces and colloids, 2024)
The Zn(II)-supramolecular metallogel (i.e., Zn-Py) of 2,6-pyridinedicarboxylic acid was prepared through the addition of a metal source and 2,6-pyridinedicarboxylic acid as a low molecular weight gelator. The Zn-Py metallogel encapsulated N,N'-dimethylformamide as gel-immobilized polar aprotic solvent media. The mechanical features of the synthesized metallogel were investigated. The thixotropic behavior of the Zn-Py metallogel was also analyzed. The microscopic feature of the metallogel was imaged through FESEM and TEM studies. The EDS pattern of the metallogel ratified the role of different gel-building chemical constituents. The stimuli responsiveness of the metallogel was also tested. The metallogel-forming mechanistic protocol was visualized through FTIR and ESI mass spectroscopic analyses. The bioeffectiveness, i.e., antimicrobial potency, of Zn-Py was also studied. The antimicrobial efficiency against both Gram +ve and Gram -ve bacteria including Salmonella typhimurium (MTCC 98), Escherichia coli (MTCC 1667), Bacillus cereus (ATCC 13061), Listeria monocytogenes (MTCC 657), and Staphylococcus aureus (MTCC 96) was critically analyzed. The FESEM images of the live bacteria and damaged bacteria due to the action of the metallogel were experimentally investigated. The Zn-Py metallogel was also used to fabricate the heterojunction and Schottky-type photodetectors to show their excellent light-matter interaction and their potentiality as active material in optoelectronics. The electrical parameters of semiconductor diodes such as the p-n junction and Schottky diode fabricated by the synthesized Zn-Py metallogel were investigated. Outcomes of the experimental investigation demonstrated that the tested metallogel effectively showed p-n junction diode parameters, especially with the ideality factor (η) of 1.3 under a dark environment. This fabricated device efficiently depicted a great ON/OFF ratio of 33.4 at a reverse bias voltage of -2 V. The metal-semiconductor-metal (M-S-M) junction-type Schottky barrier diode was also fabricated using the Zn-Py metallogel where the Au/Zn-Py metallogel/Au-based device fabrication strategy was implemented